2022
DOI: 10.3389/fnins.2022.1029473
|View full text |Cite
|
Sign up to set email alerts
|

The function of p53 and its role in Alzheimer’s and Parkinson’s disease compared to age-related macular degeneration

Abstract: The protein p53 is the main human tumor suppressor. Since its discovery, extensive research has been conducted, which led to the general assumption that the purview of p53 is also essential for additional functions, apart from the prevention of carcinogenesis. In response to cellular stress and DNA damages, p53 constitutes the key point for the induction of various regulatory processes, determining whether the cell induces cell cycle arrest and DNA repair mechanisms or otherwise cell death. As an implication, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 89 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…Canonical signaling through the WNT [15, 16], p53 [24], and NFkB [22, 23] signaling pathways have been shown to be dysregulated in AD. The WNT signaling pathway is crucial for normal brain function and neuronal survival in the adult CNS and has been extensively implicated in AD (reviewed in [15, 16]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Canonical signaling through the WNT [15, 16], p53 [24], and NFkB [22, 23] signaling pathways have been shown to be dysregulated in AD. The WNT signaling pathway is crucial for normal brain function and neuronal survival in the adult CNS and has been extensively implicated in AD (reviewed in [15, 16]).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple signaling pathways have been proposed to be dysregulated in AD, including WNT (reviewed in [15,16]), TGFβ (reviewed in [17][18][19]), mTOR (reviewed in [20,21]), NFkB (reviewed in [22,23]), p53 (reviewed in [24]), and Pi3k/Akt signaling (reviewed in [25][26][27]). Recently, multiple computational cell-cell communication (CCC) inference tools, which use single-nucleus RNA-sequencing (snRNA-seq) data to infer ligands and receptors, were developed to predict signaling patterns between cell types (reviewed in [28]).…”
Section: Introductionmentioning
confidence: 99%
“…For example, p53 loss in oligodendrocytes provided protection against subcortical white matter damage and recognition memory impairment in a white matter stroke model [39]. Moreover, various animal studies demonstrated that p53 is elevated during the initial phases of AD and other neurodegenerative conditions [40][41][42][43][44]. Potentially then, sLDR on the entire brain, or a speci c region of it, could have also some possible advantageous effect in terms of p53 reduction in the context of the natural progression of AD and likely other neurodegenerative processes.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of Bax expression elicits the release of cytochrome C, thereby instigating the process of apoptosis through the activation of caspase-3 ( An et al, 2004 ; Mizuta et al, 2007 ). Moreover, the pathogenesis of various disorders, including Alzheimer’s and Parkinson’s disease, can lead to the upregulation of Bax and caspase-3 expression, ultimately resulting in neurodegeneration ( Long et al, 2021 ; Wolfrum et al, 2022 ). In a similar vein, chemotherapeutic agents, such as DOX, have been observed to enhance the expression of Bax and caspase-3, leading to the induction of apoptosis ( Sharifi et al, 2015 ; Singh et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%